2017
DOI: 10.1007/s10712-017-9431-5
|View full text |Cite
|
Sign up to set email alerts
|

Airborne Lidar Observations of Water Vapor Variability in Tropical Shallow Convective Environment

Abstract: An airborne downward-pointing water vapor lidar provides two-dimensional, simultaneous curtains of atmospheric backscatter and humidity along the flight track with high accuracy and spatial resolution. In order to improve the knowledge on the coupling between clouds, circulation and climate in the trade wind region, the DLR (Deutsches Zentrum für Luft-und Raumfahrt) water vapor lidar was operated on board the German research aircraft HALO during the NARVAL (Next Generation Aircraft Remote Sensing for Validatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Such variability in humidity may be set on larger scales, such as dry air intrusions from mid-latitudes or moist and dry layers set by nearby deep convection [63,74], but the importance of the moisture profile above the boundary layer for radiative effects within the boundary layer remains unclear and requires further study. Recent work assesses the ability of space-borne observing systems at mapping water vapor profiles and discusses new technologies that may provide better observations of lower tropospheric water vapor that can help unravel moistureradiation interactions [75][76][77].…”
Section: Moisture-radiation Interactionsmentioning
confidence: 99%
“…Such variability in humidity may be set on larger scales, such as dry air intrusions from mid-latitudes or moist and dry layers set by nearby deep convection [63,74], but the importance of the moisture profile above the boundary layer for radiative effects within the boundary layer remains unclear and requires further study. Recent work assesses the ability of space-borne observing systems at mapping water vapor profiles and discusses new technologies that may provide better observations of lower tropospheric water vapor that can help unravel moistureradiation interactions [75][76][77].…”
Section: Moisture-radiation Interactionsmentioning
confidence: 99%
“…In parallel, the ground-based and airborne lidars and aircraft in situ measurements are vital for looking at detailed micro-/macrophysical processes associated with water vapor and its interaction with clouds. In the near term, airborne process studies such as the European NARVAL and EUREC 4 A campaigns (Kiemle et al 2017;Bony et al 2017), will pave the way for next-generation space-based water vapor measurements required to overcome existing measurement deficiencies.…”
Section: Discussionmentioning
confidence: 99%
“…They have demonstrated measurement capability in the UTLS region, as well as in cirrus clouds (Kiemle et al 2008;Groß et al 2014). Recently, airborne water vapor lidar observations focused on tropical shallow convective environments have been reported (Kiemle et al 2017), while earlier work has demonstrated the value of airborne lidar to characterize the variability of humidity and of latent heat fluxes within the convective boundary layer over land (Kiemle et al 2011).…”
Section: Measurement Capabilitiesmentioning
confidence: 99%
“…The differential absorption lidar WALES is installed pointing downwards on the HALO aircraft, measuring water vapor profiles throughout the tropical troposphere with three on-line laser wavelength positions in the near infrared situated on three water vapor absorption lines of cascading strength Kiemle et al, 2017;Gutleben et al, 2019). The weakest line, specially selected for the tropics, permits accurate profiling of very moist layers below the inversion that tops the cloud layer in the trades, while the stronger two lines provide reliable data of the moisture jump across the inversion and the dry regions above.…”
Section: Wales Lidar and Hamp Radiometermentioning
confidence: 99%
“…1b). This subset still contains small gaps mainly due to clouds, which we fill with the saturation value by assuming saturation wherever the HSRL backscatter coefficient is > 10×10 −6 m −1 sr −1 , which to sufficient approximation defines a water cloud (Kiemle et al, 2017). We deviate from this threshold only in two cases where the clouds are particularly small (on 12 August 2016 we use 5 × 10 −6 m −1 sr −1 to compensate for the signal dilution) or large (on 24 August 2016 we use 15 × 10 −6 m −1 sr −1 ).…”
Section: Wales Lidar and Hamp Radiometermentioning
confidence: 99%